12th WINFOCUS world congress on ultrasound in emergency and critical care - Acar, Y; Tezel, O; Salman, N; Cevik, E; Algaba-Montes, M; Oviedo-García, A; Patricio-Bordomás, M; Mahmoud, MZ; Sulieman, A; Ali, A; Mustafa, A; Abdelrahman, I; et al. (SpringerOpen, 2016)
A1 Point-of-care ultrasound examination of cervical spine in emergency departmentYahya Acar, Onur Tezel, Necati SalmanA2 A new technique in verifying the placement of a nasogastric tube: obtaining the longitudinal view of nasogastric tube in addition to transverse view with ultrasoundYahya Acar, Necati Salman, Onur Tezel, Erdem CevikA3 Pseudoaneurysm of the femoral artery after cannulation of a central venous line. Should we always use ultrasound in these procedures?Margarita Algaba-Montes, Alberto Oviedo-García, Mayra Patricio-BordomásA4 Ultrasound-guided supraclavicular subclavian vein catheterization. A novel approach in emergency departmentMargarita Algaba-Montes, Alberto Oviedo-García, Mayra Patricio-BordomásA5 Clinical ultrasound in a septic and jaundice patient in the emergency departmentMargarita Algaba-Montes, Alberto Oviedo-García, Mayra Patricio-BordomásA6 Characterization of the eyes in preoperative cataract Saudi patients by using medical diagnostic ultrasoundMustafa Z. Mahmoud, Abdelmoneim SuliemanA7 High-frequency ultrasound in determining the causes of acute shoulder joint painMustafa Z. MahmoudA8 Teaching WINFOCUS Ultrasound Life Support Basic Level 1 for Providers in resource-limited countriesAbbas Ali, Alrayah Mustafa, Ihab Abdelrahman, Mustafa Bahar, Osama Ali, H. Lester Kirchner, Gregor ProsenA9 Changes of arterial stiffness and endothelial function during uncomplicated pregnancyAjda Anzic, Paul LeesonA10 Cardiovascular haemodynamic properties before, during and after pregnancyAjda Anzic, Paul LeesonA11 An old man with generalized weaknessMaryam Bahreini, Fatemeh RasooliA12 Ultrasonography for non-specific presentations of abdominal painMaryam Bahreini, Houman HosseinnejadA13 Introduction of a new imaging guideline for suspected renal colic in the emergency department: effect on CT Urogram utilisationGabriel Blecher, Robert Meek, Diana Egerton-WarburtonA14 Transabdominal ultrasound screening for pancreatic cancer in Croatian military veterans: a retrospective analysis from the first Croatian veteran's hospitalEdina Ćatić Ćuti, Stanko Belina, Tihomir Vančina, Idriz KovačevićA15 The challenge of AAA: unusual case of obstructive jaundiceEdina Ćatić Ćuti, Nadan RustemovićA16 Educational effectiveness of easy-made new simulator model for ultrasound-guided procedures in pediatric patients: vascular access and foreign body managementIkwan Chang, Jin Hee Lee, Young Ho Kwak, Do Kyun KimA17 Detection of uterine rupture by point-of-care ultrasound at emergency department: a case reportChi-Yung Cheng, Hsiu-Yung Pan, Chia-Te KungA18 Abdominal probe in the hands of interns as a relevant diagnostic tool in revealing the cause of heart failureEla Ćurčić, Ena Pritišanac, Ivo Planinc, Marijana Grgić Medić, Radovan RadonićA19 Needs assessment of the potential utility of point-of-care ultrasound within the Zanzibar health systemAbiola Fasina, Anthony J. Dean, Nova L. Panebianco, Patricia S. HenwoodA20 Ultrasonographic diagnosis of tracheal compressionOliviero Fochi, Moreno Favarato, Ezio BonanomiA21 The role of ultrasound in the detection of lung infiltrates in critically ill patients: a pilot studyMarijana Grgić Medić, Ivan Tomić, Radovan RadonićA22 The SAFER Lasso; a novel approach using point-of-care ultrasound to evaluate patients with abdominal complaints in the emergency departmentYoungrock Ha, Hongchuen TohA23 Awareness and use of clinician-performed ultrasound among clinical clerkship facultyElizabeth Harmon, Wilma Chan, Cameron Baston, Gail Morrison, Frances Shofer, Nova Panebianco, Anthony J. DeanA24 Clinical outcomes in the use of lung ultrasound for the diagnosis of pediatric pneumoniasAngela Hua, Sharon Kim, James TsungA25 Effectiveness of ultrasound in hypotensive patientsIsa Gunaydin, Zeynep Kekec, Mehmet Oguzhan AyA26 Moderate-to-severe left ventricular ejection fraction related to short-term mortality of patients with post-cardiac arrest syndrome after out-of-hospital cardiac arrestJinjoo Kim, Jinhyun Kim, Gyoosung Choi, Dowon ShimA27 Usefulness of abdominal ultrasound for acute pyelonephritis diagnosis after kidney transplantationJi-Han LeeA28 Lung ultrasound for assessing fluid tolerance in severe preeclampsiaJana Ambrozic, Katja Prokselj, Miha LucovnikA29 Optic nerve sheath ultrasound in severe preeclampsiaGabrijela Brzan Simenc, Jana Ambrozic, Miha LucovnikA30 Focused echocardiography monitoring in the postoperative period for non-cardiac patientsAsta Mačiulienė, Almantas Maleckas, Algimantas Kriščiukaitis, Vytautas Mačiulis, Andrius MacasA31 POCUS-guided paediatric upper limb fracture reduction: algorithm, tricks, and tipsSharad MohiteA32 Point-of-care lung ultrasound: a good diagnostic tool for pneumonia in a septic patientZoltan Narancsik, Hugon MožinaA33 A case of undergraduate POCUS (r)evolutionSara Nikolić, Jan Hansel, Rok Petrovčič, Una Mršić, Gregor ProsenA34 The Graz Summer School for ultrasound: from first contact to bedside application: three-and-a-half-day undergraduate ultrasound training: résumé after two years of continuous developmentSimon Orlob, Markus Lerchbaumer, Niklas Schönegger, Reinhard KaufmannA35 Usefulness of point-of-care ultrasound in the emergency room in a patient with acute abdominal painAlberto Oviedo-García, Margarita Algaba-Montes, Mayra Patricio-BordomásA36 Use of bedside ultrasound in a critically ill patient. A case reportAlberto Oviedo-García, Margarita Algaba-Montes, Mayra Patricio-BordomásA37 Diagnostic yield of clinical echocardiography for the emergency physicianAlberto Oviedo-García, Margarita Algaba-Montes, Mayra Patricio-BordomásA38 Focused cardiac ultrasound in early diagnosis of type A aortic dissection with atypical presentationChun-I Pan, Hsiu-Yung Pan, Chien-Hung WuA39 Detection of imperforated hymen by point-of-care ultrasoundHsiu-yung Pan, Chia-Te KungA40 Developing a point-of-care ultrasound curriculum for pediatric nurse practitioners practicing in the pediatric emergency departmentSarah Pasquale, Stephanie J. Doniger, Sharon Yellin, Gerardo ChiricoloA41 Use of transthoracic echocardiography in emergency setting: patient with mitral valve abscessMaja Potisek, Borut Drnovšek, Boštjan LeskovarA42 A young man with syncopeFatemeh Rasooli, Maryam BahreiniA43 Work-related repetitive use injuries in ultrasound fellowsKristine Robinson, Clara Kraft, Benjamin Moser, Stephen Davis, Shelley Layman, Yusef Sayeed, Joseph MinardiA44 Lung ultrasonography in the evaluation of pneumonia in childrenIrmina Sefic Pasic, Amra Dzananovic, Anes Pasic, Sandra Vegar ZubovicA45 Central venous catheter placement with the ultrasound aid: two years' experience of the Interventional unit, Division of Intensive Care Medicine, KBC ZagrebAna Godan Hauptman, Marijana Grgic Medic, Ivan Tomic, Ana Vujaklija Brajkovic, Jaksa Babel, Marina Peklic, Radovan RadonicA46 Duplicitas casui: two patients admitted due to acute liver failureVedran Radonic, Ivan Tomic, Luka Bielen, Marijana Grgic MedicA47 A pilot survey on an understanding of Bedside Point-of-Care Ultrasound (POCUS) among medical doctors in internal medicine: exposure, perceptions, interest, and barriers to trainingPeh Wee MingA48 Unusual case of defecation syncopeNur hafiza Yezid, Fatahul Laham MohammedA49 A case report of massive pulmonary embolism; a multidisciplinary approachZainal Abidin Huda, Wan Nasarudin Wan Ismail, W.Yus Haniff W.Isa, Hashairi Fauzi, Praveena Seeva, Mohd Zulfakar Mazlan.